(untitled) (Journal of Pharmaceutical Negative Results, 2022)
NLR was considered a marker for cardiac and non-cardiac inflammation. The study aims to determine the ratio of neutrophils to lymphocytes in persons with coronary artery disease to assess inflammation.A hospital's tertiary outpatient medical section Registration began in October 2019. They were given registration information when taken to Medicine. Patients who met the study's exclusion criteria couldn't enroll during registration. The study included 72 people.The data were looked at to see if neutrophils and lymphocytes are signs of inflammation in long-term coronary artery disease. 38 of the 72 participants had single vascular disease, 23 had double, and 11 had triple. 34 single vascular disease patients had NLR 2, 3 2,1-3, and 1 3. 23 patients with bilateral vascular disease had NLRs from 1-2 to 3. NLR > 3 in 11 patients with triple vessel disease. NLR for a single coronary vessel occlusion was 1.72 + 0.52, 2.36 + 0.75, and 3.72 + 0.67. (p 0.0001).2D echo, RWMA, and angiographic studies all showed NLRs were associated with CAD.So, there was a strong link between the neutrophil-to-lymphocyte ratio (NLR) and coronary artery disease.